Molecular detection of vector-borne agents in cats in Southern Brazil - Pedrassani, Daniela; Biolchi, Juliano; Gonçalves, Luiz Ricardo [UNESP]; Mendes, Natalia Serra [UNESP]; Zanatto, Diego Carlos de Souza [UNESP]; Calchi, Ana Cláudia [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (FapUNIFESP (SciELO), 2019)
This study used serological and molecular methods to investigate the occurrence of vector-borne pathogens (VBP) with zoonotic potential in cats neutered at the University Veterinary Hospital in Canoinhas, Santa Catarina. The combined PCR and serological results revealed that 17 (56.6%) cats were positive for one or more pathogens. The sampled cats had antibodies to Ehrlichia spp. (7/30), Anaplasma phagocytophilum (3/30) and Leishmania infantum (2/30). The PCR assay detected DNA closely related to Ehrlichia canis in 6/30 cats, Mycoplasma haemofelis in 2/30 cats, A. phagocytophilum and Cytauxzoon sp. in one cat each. While Bartonella clarridgeiae and B. henselae were detected in two cats each, and B. koehlerae was detected in one cat.
Detecção molecular de agentes transmitidos por vetores em felinos domésticos no Sul do Brasil
Keywords: Anaplasma; Bartonella; Cat; Ehrlichia; Leishmania; Mycoplasma